Teaching Methods Of Character Used To The Companions Of Prophet Muhammad In Saheeh Muslim - Taufik Abdillah Syukur (Kopertais Wilayah I DKI Jakarta dan Banten, 2019)
The Government of The Republic of Indonesia instructed to each school to incorporate character education in KTSP, syllabus and lesson plans. The government has also provided BOS in order to support teachers in their teaching’s method development. The character value is good, and the teaching’s method is well developed. Why do we still find unacceptable things which refer to the weakness of nation character in the student soul? The research is talking about the prophet teaching method in building his companions character according to Shaheeh Muslim. And that result will explain about the complementation of prophet teaching method in shaping student character in the school. The teaching method is the way that used to implement the prepared program to achieve the goal of teaching. The education character is a prepared effort in order to cause the student how to know and care about the values, which finally carry on them to be the perfect man. Companion was a man who met the prophet and died in a state of faith. This study depends on the sourced literature. The researcher qualitatively collects data, describes and analyzes it well. This research is about the character teaching method depends on the prophetic tradition (al-Hadits). The researcher classifies the hadits based on nation character, analyzes that results and relates things with the main project. The result indicates that the most widely used method of the prophet in shaping his companions character is the method of story, question & answer, and also lecturer. He also used another variety method such as problem solving, assignment, demonstration and fieldtrip. In shaping his companions character he did not use the method of discussion, experiment, and project. Researcher recommends all teachers to control and widely explore those three methods (stories, discussion, and lecturer) and integrate love, friends/ communicative, and care character as the main student character in process character education at school.